The Influence of Leadership Style and Motivation on the Performance of Members of the Bogor Police Traffic Unit - R. Rizky Guntama Ganda Permana; Adriza; Sri Wahyuningsih (STMIK Indonesia Banda Aceh, 2026)
The main problem in this study is the extent to which Leadership Style and Work Motivation affect the Performance of members of the Bogor Police Traffic Unit. Leadership style and motivation are important factors that can influence individual performance within an organization. The purpose of this study is to determine and analyze the extent of the Influence of Leadership Style and Work Motivation on the Performance of members of the Bogor Police Traffic Unit, both partially and simultaneously. The method used in this study is a quantitative method with a descriptive and verification approach. The sample used consisted of 72 respondents, selected through random sampling. The data in this study were obtained from respondents' answers to a questionnaire distributed by the author. The results of the data analysis show that leadership style has a positive and significant effect on members' performance. Likewise, work motivation has a positive and significant effect on performance. Simultaneously, Leadership Style and Work Motivation affect the Performance of members of the Bogor Police Traffic Unit.